2015
DOI: 10.1016/j.gexplo.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemistry and its controlling factors of rivers in the source region of the Yangtze River on the Tibetan Plateau

Abstract: This study focuses on the chemical composition, and the factors controlling it, of the high mountain-rivers in the source region of the Yangtze River on the Tibetan Plateau. By comprehensive and systematic analysis, the chemical signatures, spatial variations of water quality, as well as the factors controlling them are studied. The value of the average total dissolved solids (TDS) is 778 mg/l, ranging from 117 to 5496 mg/l. In order of decreasing concentration, the main cations are Na try of the river water i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 37 publications
2
59
1
4
Order By: Relevance
“…Evidence showed that the lack of correlations between Cland SO 4 2can be the signature of sulfate oxidation (Galy & France-Lanord, 1999;Hren et al, 2007). However, Cland SO 4 2showed significant positive correlations in YRSR water chemistry data from this study (R 2 = 0.58, p < 0.001), Qu et al (2019) data set (R 2 = 0.53, p = 0.001), and Jiang et al (2015) data set (R 2 = 0.57, p < 0.001). Besides, pyrite oxidation can lead to high Si and SO 4 2but low bicarbonate concentrations (Huh, Panteleyev, et al, 1998;Huh, Tsoi, et al, 1998).…”
Section: Water Resources Researchmentioning
confidence: 74%
See 4 more Smart Citations
“…Evidence showed that the lack of correlations between Cland SO 4 2can be the signature of sulfate oxidation (Galy & France-Lanord, 1999;Hren et al, 2007). However, Cland SO 4 2showed significant positive correlations in YRSR water chemistry data from this study (R 2 = 0.58, p < 0.001), Qu et al (2019) data set (R 2 = 0.53, p = 0.001), and Jiang et al (2015) data set (R 2 = 0.57, p < 0.001). Besides, pyrite oxidation can lead to high Si and SO 4 2but low bicarbonate concentrations (Huh, Panteleyev, et al, 1998;Huh, Tsoi, et al, 1998).…”
Section: Water Resources Researchmentioning
confidence: 74%
“…The covariance of temperature, thaw depth, and discharge during the thawed period may enhance silicate weathering; this can be supported by the results of Si increasing with thaw depth, soil temperature, soil moisture, and discharge ( Figure S5). When the active layer fully thawed in the summer, microbial activity increased as This study Qu et al, 2015Zhao et al, 2019Jiang et al, 2015Huang et al, 2009 Note. Each data set was modeled with same end-members as shown in Table S1 using MixSIAR.…”
Section: Interpretation Of Dic and δ 13 C-dic Variationsmentioning
confidence: 91%
See 3 more Smart Citations